Multi-pass solar air heating collector system for drying of screw-pine leaf (Pandanus tectorius) - Kareem, M.W. (Elsevier Ltd, 2017)
An experimental investigation of solar drying of screw-pine leaf has been conducted in the open space of the solar research site, Universiti Teknologi PETRONAS Malaysia (4.385693° N, 100.979203° E). Screw-pine leaf has been used for handcraft in many villages in Asia and Africa. A transient state lumped element analysis was developed to determine the thermal performance of the multi-pass solar collector system (MSCS) in accordance with ASHRAE standards. The facility was assessed under the average daily solar irradiance of 412.6 Wm−2 and ambient temperature of 30 °C over an air mass flow rate range from 0.010 kgs−1 to 0.032 kgs−1. Drying kinetics profiles of screw-pine have been obtained and an improved range from 22 to 26 of instantaneous thermal collector efficiency has been recorded over the double pass collector system (DPCS) while thermal energy storage has contributed 5–8 to system performance. MSCS performance has been determined and achieved the thermal collector, pickup, drying and exergy efficiencies of 58.73, 66.95, 36.04 and 27.23–86.82, respectively. The level of risk on the investment in MSCS has been measured using economic indices to obtain a payback period of 0.75 year. The thermal loss through conventional collector back plate has been prevented by integration of collector unit and the drying cabinet of the system. There is still need to further improve the system performance efficiency through enhanced energy saving innovation technique. © 2017 Elsevier Ltd